الضغوط النفسية وعلاقتها بالاحتراق النفسي - حزام, أسماء (Université de M'sila, 2016)
The subject of Psychological stress and psychological burn is one of the recent studies that have shown greater levels of interest among pedagogic community. This study aims to answer the following questions: - What is the Psychological stress level that the principals and supervisors of girl's secondary schools at Riyadh are suffering from? - What is the Psychological burn level that the principals and supervisors of girls' secondary schools at Riyadh are suffering from? - Is there any significant statistic correlation between Psychological stress and Psychological burn that might be available with the principals and supervisors of girls' secondary schools at Riyadh? We followed the descriptive style in this research and we formed a sample of 200 principals and supervisors. The tools were represented in Psychological burn scale and Psychological stress scale. The study's conclusion states that Psychological burn is an advanced phase of continuous and persisting stress, whereas the correlation between stress and burn is like the correlation between a private and a general concern. Stress affects many people as it is considered one of our life basics: and it is then a motivation for a better life. On the other hand, burn affects people when stress increases continuously till they become unable to accommodate with such situation. This symptom is not applicable on all people. Accordingly, each burnt individual suffers from stress and not the opposite.
Keywords: الضغوط / النفسية / الاحتراف